Contemporary educational perspective: Teacher success or failure? - Mello, Cidnei Amaral de; Benites, Maira Cristiane (Seven Editora, 2024)
This article brings a reflection on teacher training in the face of an interconnected society, where information is made immediately, reaching the most different community groups, directly and abruptly inducing School Education.  During teacher training, most of the time they do not learn how to work with so many challenges, with uncertainty and the unexpected, which are consequences of current events, and often their professional function masked by situations that involve the student requires the teacher to act with multitasking. The cultural and family differences that are poured into the school end up inciting under the teaching work a veiled anovelling of situations that stand out from their primary attributions, that of teaching, which generates an excess of overload in the exercise of the profession and in addition to countless demands. The school community, in turn, seems to forget that the teaching work has the human being as an instrument, which makes the pedagogical act intricate, as it is essential to welcome several students in their entirety and not only in pedagogical issues, understanding that other issues such as emotional ones are directly linked to learning. We present here through a bibliographic review this analysis  with a descriptive-analytical character, which involved collection, systematization of reports produced with this theme and it was observed such discrepancy and with a technological world, the teacher still needs to compete in turn gets sick, without realizing it and without having the necessary support to deal with so many adverse circumstances, where technology should be treated as its ally and a tool for diversification methodological, but it is causing difficulties in carrying out their hard and daily work. DOI:https://doi.org/10.56238/sevened2023.008-028